Qualitative traits and genetic characterization of native chicken (Gallus gallus domesticus) in selected areas of Eastern and Western Samar, Philippines - Godinez, Cyrill John P.; Nishibori, Masahide; Espina, Dinah M. (Annals of Tropical Research, 2020)
The Philippines has a number of chicken genetic groups, mostly of non-descript and indigenous type. In view of the need to expand the information on native chicken diversity, this study was conducted to identify distinct qualitative traits and estimate genetic diversity and relationship among native chicken populations in selected areas of Eastern and Western Samar, Philippines. A total of 100 native chickens were qualitatively analyzed using a non-parametric test, and 43 generated mtDNA sequences were used in the genetic analysis. Results revealed significantly different distributions of plumage color among male native chickens and shank color in female native chickens (p<0.05). The occurrence of plumage pattern, earlobe color and shank color for male native chickens and plumage color, plumage pattern, and earlobe color for female native chickens across Samar Island is not different (p>0.05). The genetic relationship showed 41.2% native chicken populations clustered to a group shared by Red junglefowl and native chicken, 29.4% clustered to a group closer to White Leghorn, and White Plymouth Rock chicken breeds, 17.6% clustered to a group shared by G. g. spadiceus and a commercial line, and 11.7% clustered to a group closer to Rhode Island Red and a commercial egg layer line. Samar native chickens had red (wild-type, e+) laced (lg) and brown (eb) pencilled (Pg) plumage in rooster and hen, respectively. The phenotypic and genetic information concluded that there is considerable diversity of native chickens in Samar, Philippines. There is a tremendous opportunity to work with larger sample size in the areas where a number of indigenous chickens have not yet been characterized.